Newman and Strossmayer on the Relationship Between the Church and the State (II) - Šokčević, Šimo; Živić, Tihomir (Anafora, 2023)
The cooperation between the Catholic Church and the State is a necessity and an imperative that was addressed by two important thinkers of the 19th century, John Henry Newman and Josip Juraj Strossmayer, and the models that actually trace back to their reflections are existent even nowadays. In the second part of a textological and theological analysis of Newman’s and Strossmayer’s understanding of the relationship between the Church and the State, our objective is to explore how much Newman’s and Strossmayer’s deliberationsmay be useful in the formulation of the bases on which a good relationship between the Catholic Church and the State should be built. We have seen that comprehension and concord are the fundamental imperatives of that relationship, as well as of the contemporary models that analyze it. The modern obstacles to this relationship have the identical roots, findable in negative liberalism and repaganization. On the trail of Newman and Strossmayer, we onclude that an anthropological reform primarily taking hold of the human heart is necessary today. Therefore, such a reform has to realize that the life in accordance with one’s own conscience, in the truth, is more valuable than all the utopian lies and deceptions that formulate the socioeconomic relations and personal life.